Perlindungan Hukum Terhadap Pekerja Rumah Tangga Di Kelurahan Suka Karya Kota Jambi Berdasarkan Peraturan Menteri Ketenagakerjaan - Ageng Triganda Sayuti; Tengku Maizura Hakim (Universitas Jambi, Fakultas Hukum, 2021)
Everyone has the right to get a decent job, as well as get a wage, including one of them is a Domestic Worker, Domestic Workers must get the same protection, based on the problems above, the writing draws two formulations of the problem as follows, First, How is the Implementation of Legal Protection for Domestic Workers in Suka Karya Village, Jambi City?, Second, what are the obstacles that occur in the implementation of legal protection for domestic workers in Suka Karya Village, Jambi City?. This study aims to determine and analyze how the form of protection for domestic workers, and what obstacles occur in the enforcement of legal protection for domestic workers in Suka Karya Village, Jambi City. This writing uses the Juridical Empirical method due to the difference between the Legislation and what actually happened in the community, with a sample of 76 respondents, namely 38 domestic workers and 38 domestic worker service users, so that the results obtained are two legal protection probematics. For domestic workers, first, there are 30 respondents who use domestic workers services who do not include domestic workers in the Social Security program and second, there are 21 respondents who use domestic workers do not report the use of domestic workers to the head of the Neighborhood Association, while the obstacles that arise are: faced is due to the lack of legal awareness of the community in carrying out legal protection for domestic workers, so it is necessary to enforce strict sanctions on elements that use domestic workers services who violate their obligations. the Minister of Manpower or specifically the Manpower Office to provide socialization on how to protect domestic workers. Abstrak Setiap orang memiliki hak untuk mendapatkan pekerjaan yang layak, serta mendapatkan upah, termasuk salah satunya adalah Pekerja Rumah Tanga, Pekerja Rumah Tangga harus mendapatkan Perlindungan yang sama, berdasarkan permasalahan diatas maka penulisan menarik dua rumusan masalah sebagai berikut, Pertama, Bagaimana Pelaksanaan Perlindungan Hukum bagi Pekerja Rumah Tangga di Kelurahan Suka Karya Kota Jambi?, Kedua, Apa saja kendala yang terjadi dalam pelaksanaan Perlindungan Hukum bagi pekerja rumah tangga di Kelurahan Suka Karya Kota Jambi?. Penelitian ini bertujuan untuk mengetahui dan menganalisis bagaimana bentuk perlindungan pekerja rumah tangga, dan kendala apa saja yang terjadi dalam penegakan perlindungan hukum terhadap perkerja rumah tangga di Kelurahan Suka Karya Kota Jambi. Penulisan ini menggunakan metode Yuridis Empiris dikarenakan terjadinya Perbedaan antara Peraturan Perundang-Undangan dengan yang terjadi sebenarnya di masyarakat, dengan dengan sampel 76 responden, yaitu 38 orang pekerja rumah tangga dan 38 orang pengguna jasa pekerja rumah tangga, sehingga diperoleh hasil terdapat dua probematika Perlindungan Hukum Bagi Pekerja Rumah Tangga, yaitu pertama terdapat 30 responden Pengguna jasa Pekerja Rumah Tangga yang tidak mengkutsertakan pekerja rumah tangga dalam program Jaminan Sosial dan Kedua, terdapat 21 Responden Pengguna Jasa Pekerja Rumah Tangga tidak melaporkan penggunaan Pekerja Rumah Tangga Kepada Ketua Rukun Tetangga, sedangkan kendala yang dihadapi adalah dikarenakan kurangnya kesadaran hukum masyarakat dalam melaksanakan perlindungan Hukum bagi pekerja rumah tangga, sehingga diperlukan penegakan sanksi yang tegas kepada para oknum-oknum pengguna jasa pekerja rumah tangga yang melanggar kewajibannya.saran berikutnya adalah diperlukan peran Menteri Ketenegakerjaan atau secara spesifik Dinas Ketenagakerjaan untuk memberikan sosialisasi tentang bagaimana perlindungan hukum pekerja rumah tangga.